2020
DOI: 10.1177/2324709620936808
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitors’ Newly Reported Endocrine Side Effect: Pazopanib-Induced Primary Adrenal Insufficiency in a Patient With Metastatic Renal Cell Cancer

Abstract: Tyrosine kinase inhibitors (TKIs) have been used in the treatment of multiple types of cancer. Pazopanib is one of the TKIs and is considered a first-line treatment for adult patients with metastatic renal cell carcinoma. Many endocrine-related adverse effects have been noted with the use of TKIs including hypothyroidism, vitamin D deficiency, altered bone density, secondary hyperparathyroidism, abnormal glucose metabolism, gynecomastia, and hypogonadism. Subclinical glucocorticoid deficiency and adrenal insuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Further to this, Elshimy et al [3] have reported a case of primary adrenal insufficiency in the setting of pazopanib therapy for mRCC. This patient had previously undergone unilateral nephrectomy and adrenalectomy, but had no documented history of hypoadrenalism.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Further to this, Elshimy et al [3] have reported a case of primary adrenal insufficiency in the setting of pazopanib therapy for mRCC. This patient had previously undergone unilateral nephrectomy and adrenalectomy, but had no documented history of hypoadrenalism.…”
Section: Discussionmentioning
confidence: 92%
“…Subsequent investigations demonstrated hypoadrenalism, and secondary causes were all ruled out. Thus, this was reported as a case of primary adrenal insufficiency associated with pazopanib therapy [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PAI induced by pazopanib has been reported in a patient affected by metastatic kidney cancer [63]. No specific measure aimed at monitoring and preventing the risk of AI are cautioned for patients under these TKIs.…”
Section: Tki-induced Adrenal Insufficiencymentioning
confidence: 99%
“…3 So far, one case of pazopanib associated primary adrenal insufficiency has been reported in the literature. 4 To the best of our knowledge, no case reporting secondary adrenal insufficiency due to pazopanib has been reported.…”
Section: Introductionmentioning
confidence: 95%